Iridium-based nanoparticle catalyst as well as preparation method and application thereof
By mixing metal Ir salt, metal M salt and alkali compound in proportion, drying and high-temperature annealing, an iridium-based nanoparticle catalyst with an average particle size of 5-15 nm was prepared, and the existing iridium-based catalyst has large particle sizes. The problem of low catalytic activity has achieved efficient and low-cost catalyst production.
Patent Information
- Application Number
- CN202411408497.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-11
AI Technical Summary
In PEM electrolytic technology, existing iridium-based catalysts have large particle sizes and low catalytic activity, complex production steps and difficult to mass-produce on a large scale, and the precious metal iridium has a high load and high cost.
By mixing and grinding metal Ir salt, metal M salt and alkali compound in proportion, forming a precursor powder, then mixing it thoroughly with the solvent and drying it, and finally undergoing high-temperature annealing treatment to prepare iridium-based nanoparticles with an average particle size of 5-15 nm catalyst.
A simple and easy-to-use catalyst preparation method is realized, which reduces the load of the precious metal iridium, improves catalytic activity, is suitable for mass production, and avoids the generation of harmful substances.
Smart Images

Figure CN119406404A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water electrolysis catalysts, and in particular to an iridium-based nanoparticle catalyst and a preparation method and application thereof. Background Art
[0002] Proton exchange membrane (PEM) water electrolysis technology has many advantages such as low energy consumption, high efficiency, good hydrogen quality, and reliable operation. In particular, it has high flexibility and excellent power regulation function, which is very suitable for the volatility of renewable energy such as wind, light, and water. At present, the oxygen evolution catalyst of commercial PEM electrolyzer is iridium-based catalyst represented by IrO2, and the iridium loading of membrane electrode is usually as high as 2-4mg / cm 2 . Iridium resources are extremely scarce and expensive, so at this stage we need to work hard to significantly reduce the amount of iridium used. The use of appropriate catalyst carriers can help reduce the load of precious metals and improve catalytic performance. However, the strong acid and strong oxidizing working environment of the anodic oxygen evolution reaction makes it difficult for traditional carrier materials (such as carbon, metal oxides, etc.) to achieve ideal results. Therefore, it is very important to design and synthesize new iridium-based catalysts with high conductivity, strong corrosion resistance, and large specific surface area.
[0003] At present, the main technical routes for preparing iridium-based catalysts include the Adams melt method, liquid phase reduction method, template method and sol-gel method. Specifically, the Adams melt method involves reacting the iridium precursor with excess sodium nitrate to generate the corresponding iridium salt, which is then dried and oxidized at high temperature to finally produce iridium oxide. This method produces a large amount of NO xHazardous substances need further treatment (Electrochimica Acta 56 (2011) 10223-10230, International Journal of Hydrogen Energy 45 (2020) 1409-1416). Both the liquid phase reduction method and the template method involve high-cost raw materials such as metal organic complexes, templates, reducing agents, surfactants, organic solvents, etc., which are not conducive to mass production and will produce a large amount of organic wastewater (CN104437481B, CN103055853B, Adv Nat Sci: Nanosci Nanotechnol 6 (2015) 025015). The sol-gel method is also a commonly used method for preparing iridium-based nanoparticles. This method controls the hydrolysis and polycondensation reaction of the precursor in the solution to form a sol, and then obtains nanoparticles through multiple steps such as gelation, drying and calcination (Journal of Applied Electrochemistry 39 (2009) 2093-2105). Iridium-based catalysts prepared by these traditional methods generally face problems such as large particle size, low catalytic activity, complicated production steps, difficulty in large-scale mass production, and impurities mixed in the products. These problems make it difficult to meet the demand for iridium-based catalysts during the actual operation of PEM electrolyzers. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide an iridium-based nanoparticle catalyst and a preparation method and application thereof. The preparation method is simple and easy, has a wide adaptability, and can mass-produce iridium-based nanoparticle catalysts with small particle sizes. By adjusting the proportion of metal salts, the iridium content in the iridium-based nanoparticle catalyst is controlled, the loading amount of the precious metal iridium is effectively reduced, and the cost is reduced. The prepared catalyst has high catalytic activity and meets the demand for iridium-based catalysts during the actual operation of a PEM electrolyzer.
[0005] In order to solve the above technical problems, the present invention provides a method for preparing an iridium-based nanoparticle catalyst, comprising the following steps:
[0006] S1, mixing a metal Ir salt, a metal M salt and an alkali compound and grinding them for 20-60 minutes to obtain a precursor powder;
[0007] Wherein, the molar ratio of the metal Ir salt, the metal M salt and the base compound is 1:(1-5):(5-20);
[0008] S2, adding a solvent to the precursor powder, allowing the solvent and the precursor powder to fully mix and react, and after the gas generated by the reaction is completely discharged, grinding for 10-30 minutes to obtain a slurry-like mixture;
[0009] Wherein, the volume ratio of the solvent to the precursor powder is (1-3):1;
[0010] S3, placing the slurry mixture in a blast constant temperature drying oven to dry it to obtain a dry mixture;
[0011] S4, dispersing the dry mixture into powder, and transferring it to a high temperature furnace and keeping it at 200-500° C. for 0.5-5 h for annealing to obtain an iridium-based nanoparticle catalyst with an average particle size of 5-15 nm.
[0012] The invention mixes metal Ir salt, metal M salt and alkali compound in proportion and grinds them to obtain precursor powder, mixes the precursor powder with solvent and grinds them to obtain a slurry mixture, anneals the mixture after drying to obtain iridium-based nanoparticle catalyst; the preparation method is simple, only mechanical grinding, drying and high-temperature annealing steps are required, and it is convenient and easy; and the preparation method does not involve high-cost raw materials such as organic solvents, surfactants, complexing agents, etc., thus avoiding the generation of organic wastewater; in addition, there is no need to add excessive sodium nitrate, thus avoiding the generation of a large amount of NO x The present invention has many raw materials to choose from, and can be coupled with a variety of non-precious metals to prepare a variety of iridium-based nanoparticle catalysts; and can effectively reduce the loading amount of precious metal iridium by adjusting the proportion of metal salts fed to control the proportion of iridium content in the nanoparticle product.
[0013] The catalyst prepared by the method of the present invention is a particle with an average particle size of 5-15nm, a small particle size, and a high specific surface area, and its specific surface area can reach 50-80m 2 g -1 , which is conducive to material transfer and exchange, and thus has better catalytic activity than traditional catalyst materials.
[0014] Furthermore, in S1, the metal Ir salt is one or more of iridium chloride, iridium acetate, chloroiridic acid, and potassium chloroiridate.
[0015] Furthermore, in S1, the metal M salt is one or more of the chloride, nitrate, sulfate, and phosphate of metal M, and the metal M is one or more of Zr, Mo, Ta, Sn, Fe, Co, Ni, Cu, Zn, Y, Cd, and In.
[0016] Furthermore, in S1, the alkaline compound is one or more of ammonium carbonate, ammonium bicarbonate, ammonium chloride, ammonium oxalate, ammonium sulfate, ammonium hydroxide, ammonium nitrate, sodium hydroxide, and potassium hydroxide.
[0017] Furthermore, in S3, the drying temperature is 70-90° C. and the drying time is 24-48 hours.
[0018] Furthermore, in S4, the dispersing method is grinding or ultrasound.
[0019] Furthermore, in S4, the heating rate of the annealing is 1-5°C / min, the annealing atmosphere is argon, nitrogen or air, and the annealing pressure is normal pressure.
[0020] Furthermore, in S4, the high temperature furnace is a tube furnace, a muffle furnace, a box furnace, a pit furnace, an atmosphere furnace, etc.
[0021] Furthermore, in S1 and S2, the container used for grinding is an agate mortar, a glass mortar, a ceramic mortar, a high-energy ball mill, an intermittent ball mill, a column mill, a rod mill, a tube mill, a mortar-type roller mill, a multi-layer vertical mill, a vertical roller mill or a disc mill, etc.
[0022] Furthermore, in S2, the solvent is one or more of deionized water, ethanol, and isopropanol.
[0023] The second aspect of the present invention provides an iridium-based nanoparticle catalyst prepared by the preparation method of the first aspect, wherein the catalyst has a molecular formula of Ir x -M y -O 1-x-y Indicates that, 0.05≤x≤0.2, 0.25≤y≤0.4.
[0024] The third aspect of the present invention provides the use of the iridium-based nanoparticle catalyst described in the second aspect, wherein the iridium-based nanoparticles are used as anode catalysts in a proton exchange membrane water electrolysis device.
[0025] Beneficial effects of the present invention:
[0026] The preparation method of the iridium-based nanoparticle catalyst of the present invention comprises the following steps: mixing metal Ir salt, metal M salt and alkali compound in proportion, grinding and dissolving, and then drying and annealing to obtain the iridium-based nanoparticle catalyst; the preparation method is simple, requiring only mechanical grinding, drying and high-temperature annealing steps, and is convenient and easy to perform.
[0027] The preparation method of the present invention does not involve high-cost raw materials such as organic solvents, surfactants, and complexing agents, thereby avoiding the generation of organic wastewater; in addition, there is no need to add excessive sodium nitrate, thereby avoiding the generation of a large amount of NO x The present invention has many raw materials to choose from, and can be coupled with a variety of non-precious metals to prepare a variety of iridium-based nanoparticle catalysts; and can effectively reduce the loading amount of precious metal iridium by adjusting the proportion of metal salts fed to control the proportion of iridium content in the nanoparticle product.
[0028] The catalyst prepared by the method of the present invention is a particle with an average particle size of 5-15nm, a small particle size, and a high specific surface area, which is as high as 50-80m 2 g -1 , which is conducive to material transfer and exchange, and thus has better catalytic activity than traditional catalyst materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Ir prepared in Example 1 of the present invention x -Zr y -O 1-x-y SEM image of nanoparticle catalyst;
[0030] Figure 2 Ir prepared in Example 1 of the present invention x -Zr y -O 1-x-y Energy spectrum of nanoparticle catalyst;
[0031] Figure 3 Ir prepared in Example 2 of the present invention x -Mo y -O 1-x-y SEM image of nanoparticle catalyst;
[0032] Figure 4 Ir prepared in Example 2 of the present invention x -Mo y -O 1-x-y Energy spectrum of nanoparticle catalyst;
[0033] Figure 5 Ir prepared in Example 3 of the present invention x -Ta y -O 1-x-y SEM image of nanoparticle catalyst;
[0034] Figure 6 Ir prepared in Example 3 of the present invention x -Ta y -O 1-x-y Energy spectrum of nanoparticle catalyst;
[0035] Figure 7 It is a comparison chart of oxygen evolution performance test of iridium-based nanoparticle catalysts prepared in Examples 1-3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0036] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0037] Example 1
[0038] This embodiment relates to an Ir x -Zr y -O 1-x-y The preparation method of nanoparticle catalyst comprises the following steps:
[0039] (1) Selecting raw materials of metal Ir salt, metal M salt and alkali compound as iridium acetate, zirconium hydrogen phosphate and ammonium hydrogen carbonate, respectively, and weighing powders in a molar ratio of 1:5:20, putting the above raw materials into an agate mortar and grinding them with a pestle for 20 minutes to fully mix the raw materials to obtain a precursor powder.
[0040] (2) Add sufficient deionized water to the precursor powder prepared in step (1) to completely dissolve it. After the bubbles generated by the reaction completely disappear, grind it with an agate mortar for 10 minutes to form a uniform slurry mixture, wherein the volume ratio of the solvent to the precursor powder is 2:1.
[0041] (3) The slurry mixture prepared in step (2) is transferred to a porcelain boat, and the porcelain boat containing the mixture is placed in a blast constant temperature drying oven at 80° C. for 48 hours until it is completely dry.
[0042] (4) The dried mixture in step (3) is taken out from the drying oven, transferred to an agate mortar, the agglomerated mixture is dispersed into powder, and then transferred to a tube furnace, and the temperature is increased to 300° C. at a heating rate of 5° C. / min in an air atmosphere, kept at this temperature for 2 hours, and then naturally cooled to room temperature.
[0043] (5) The Ir prepared in step (4) x -Zr y -O 1-x-y The nanoparticle catalyst was stored in a drying oven at 20 °C for further structural characterization and electrocatalytic analysis.
[0044] The Ir prepared in this example x -Zr y -O 1-x-y The nanoparticle catalysts were subjected to scanning electron microscopy analysis, such as Figure 1 As shown in Figure 2, the catalyst has a granular morphology with an average particle size of about 10 nm and a specific surface area of 50-80 m 2 g -1 The Ir prepared in this example x -Zr y -O 1-x-y Energy spectrum analysis of nanoparticle catalysts, reference Figure 2It can be seen that the chemical composition of the catalyst is oxygen, zirconium and iridium, and the three are evenly distributed in the particle catalyst. The weight percentage and atomic number percentage of oxygen, zirconium and iridium in the catalyst are shown in Table 1.
[0045] Table 1
[0046] element Weight % Atomic% O 21.58 64.59 Zr 57.55 30.21 Ir 20.87 5.20
[0047] Example 2
[0048] This embodiment relates to an Ir x -Mo y -O 1-x-y The preparation method of nanoparticle catalyst comprises the following steps:
[0049] (1) Selecting raw materials of metal Ir salt, metal M salt and alkali compound as iridium chloride, molybdenum chloride and ammonium bicarbonate, respectively, and weighing powders in a molar ratio of 1:2:8, putting the above raw materials into a glass mortar and grinding them with a pestle for 30 minutes to fully mix the raw materials to obtain a precursor powder.
[0050] (2) Add sufficient ethanol to the precursor powder prepared in step (1) to completely dissolve it. After the bubbles generated by the reaction completely disappear, grind it with a glass mortar for 20 minutes to form a uniform slurry mixture, wherein the volume ratio of the solvent to the precursor powder is 1.5:1.
[0051] (3) The slurry mixture prepared in step (2) is transferred to a porcelain boat, and the porcelain boat containing the mixture is placed in a forced air constant temperature drying oven at 80° C. for 24 hours until it is completely dry.
[0052] (4) The dried mixture in step (3) is taken out from the drying oven, transferred to an agate mortar, the agglomerated mixture is dispersed into powder, and then transferred to a tube furnace, and the temperature is increased to 400° C. at a heating rate of 5° C. / min in an air atmosphere, kept at this temperature for 2.5 hours, and then naturally cooled to room temperature.
[0053] (5) The Ir prepared in step (4) x -Mo y -O 1-x-y The nanoparticle catalyst was stored in a drying oven at 20 °C for further structural characterization and electrocatalytic analysis.
[0054] The Ir prepared in this example x -Mo y -O 1-x-y The nanoparticle catalysts were subjected to scanning electron microscopy analysis, such as Figure 3 As shown, the catalyst has a granular morphology, and the average particle size is about 10nm. x -Moy -O 1-x-y Energy spectrum analysis of nanoparticle catalysts, reference Figure 4 It can be seen that the chemical composition of the catalyst is oxygen, molybdenum and iridium, and the three are evenly distributed in the particle catalyst. The weight percentage and atomic number percentage of oxygen, molybdenum and iridium in the catalyst are shown in Table 2.
[0055] Table 2
[0056] element Weight % Atomic% O 14.86 58.03 Mo 43.82 28.54 Ir 41.32 13.43
[0057] Example 3
[0058] This embodiment relates to an Ir x -Ta y -O 1-x-y The preparation method of nanoparticle catalyst comprises the following steps:
[0059] (1) Selecting raw materials of metal Ir salt, metal M salt and alkaline compound as chloroiridic acid, tantalum pentachloride and ammonium carbonate, respectively, and weighing powders in a molar ratio of 1:1:5, putting the above raw materials into an agate mortar and grinding them with a pestle for 25 minutes to fully mix the raw materials to obtain a precursor powder.
[0060] (2) Add a sufficient amount of isopropanol to the precursor powder prepared in step (1) to completely dissolve it. After the bubbles generated by the reaction completely disappear, grind it with an agate mortar for 10 minutes to form a uniform slurry mixture, wherein the volume ratio of the solvent to the precursor powder is 2:1.
[0061] (3) The slurry mixture prepared in step (2) was transferred to a porcelain boat, and the porcelain boat containing the mixture was placed in a constant temperature drying oven with a forced air flow at 80° C. for 36 hours until it was completely dry.
[0062] (4) The dried mixture in step (3) is taken out from the drying oven, transferred to an agate mortar, the agglomerated mixture is dispersed into powder, and then transferred to a tube furnace, and the temperature is increased to 350° C. at a heating rate of 5° C. / min in an air atmosphere, kept at this temperature for 2 hours, and then naturally cooled to room temperature.
[0063] (5) The Ir prepared in step (4) x -Ta y -O 1-x-y The nanoparticle catalyst was stored in a drying oven at 20 °C for further structural characterization and electrocatalytic analysis.
[0064] The Ir prepared in this example x -Ta y -O 1-x-y The nanoparticle catalysts were subjected to scanning electron microscopy analysis, such as Figure 5As shown, the catalyst has a granular morphology, and the average particle size is about 10nm. x -Ta y -O 1-x-y Energy spectrum analysis of nanoparticle catalysts, reference Figure 6 It can be seen that the chemical composition of the catalyst is oxygen, tantalum and iridium, and the three are evenly distributed in the particle catalyst. The weight percentage and atomic number percentage of oxygen, tantalum and iridium in the catalyst are shown in Table 3.
[0065] Table 3
[0066] element Weight % Atomic% O 7.91 49.85 Ta 56.55 31.51 Ir 35.54 18.64
[0067] Comparative Example 1
[0068] The difference between this comparative example and Example 1 is that when the tubular furnace is used for annealing, the temperature is 800°C and the holding time is 8 hours, and the other steps remain unchanged. The catalyst prepared in this comparative example is analyzed by scanning electron microscope, and it is found that its average particle size is 100-350nm, which is relatively large.
[0069] Comparative Example 2
[0070] This comparative example relates to a method for preparing an IrO2 catalyst, comprising the following steps:
[0071] (1) Dissolving chloroiridic acid in deionized water to obtain a chloroiridic acid solution, wherein the mass concentration of the solution is 10%; weighing 10.5 g of the chloroiridic acid solution, 20 g of ethylene glycol, and 10 g of a sodium carbonate aqueous solution (mass concentration 10%), placing them in a beaker and ultrasonically dispersing them for 30 minutes to obtain a mixed solution.
[0072] (2) The mixed solution was placed in a three-necked flask, 1 g of formic acid was added, and the mixture was reacted in a water bath at 80° C. with magnetic stirring for 2 hours to obtain a reaction solution.
[0073] (3) The reaction solution was centrifuged and washed, and then dried in an air drying oven at 70° C. for 3 hours to obtain a catalyst precursor.
[0074] (4) The catalyst precursor is placed in a tubular furnace and heat treated at 450°C for 2 hours in an air atmosphere. After natural cooling, the catalyst is washed and filtered with deionized water, and then dried at 70°C in air to obtain the desired IrO2 catalyst.
[0075] Test Case
[0076] The oxygen evolution performance of the nanoparticle catalysts prepared in Examples 1-3 and Comparative Examples 1-2 was tested at room temperature, the test system was a standard three-electrode system, the counter electrode was a carbon rod, the reference electrode was a saturated calomel electrode, and the electrolyte was a 0.5M H2SO4 aqueous solution saturated with nitrogen. Figure 7 As shown, the catalysts obtained in Examples 1-3 only require overpotentials of 335 mV, 286 mV, and 314 mV, respectively, to provide 10 mA cm -2 The catalyst obtained in Comparative Example 1 requires an overpotential of 478 mV to provide 10 mA cm -2 The reason is mainly because the nanoparticle catalyst prepared in the embodiment of the present invention has a smaller average particle size, thus having a higher specific surface area and excellent catalytic activity, while the comparative example 1 is annealed at a higher temperature, the catalyst particle size is larger, the specific surface area is smaller, and the catalytic activity is relatively poor. In addition, it is known from tests that the overpotential of the IrO2 catalysis prepared in the comparative example 2 is 570mV, which is much greater than the overpotential of the catalyst obtained in the embodiment of the present invention. It can be seen that the catalyst prepared in the embodiment of the present invention has excellent catalytic activity.
[0077] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A method for preparing an iridium-based nanoparticle catalyst, characterized in that: The steps include: S1, mixing a metal Ir salt, a metal M salt and an alkali compound and grinding them for 20-60 minutes to obtain a precursor powder; Wherein, the molar ratio of the metal Ir salt, the metal M salt and the base compound is 1:(1-5):(5-20); S2, adding a solvent to the precursor powder, allowing the solvent and the precursor powder to fully mix and react, and after the gas generated by the reaction is completely discharged, grinding for 10-30 minutes to obtain a slurry-like mixture; Wherein, the volume ratio of the solvent to the precursor powder is (1-3):1; S3, placing the slurry mixture in a blast constant temperature drying oven to dry it to obtain a dry mixture; S4, dispersing the dry mixture into powder, and transferring it to a high temperature furnace and keeping it at 200-500° C. for 0.5-5 h for annealing to obtain an iridium-based nanoparticle catalyst with an average particle size of 5-15 nm.
2. The method for preparing the iridium-based nanoparticle catalyst according to claim 1, characterized in that: In S1, the metal Ir salt is one or more of iridium chloride, iridium acetate, chloroiridic acid, and potassium chloroiridate.
3. The method for preparing the iridium-based nanoparticle catalyst according to claim 1, characterized in that: In S1, the metal M salt is one or more of the chloride, nitrate, sulfate, and phosphate of metal M, and the metal M is one or more of Zr, Mo, Ta, Sn, Fe, Co, Ni, Cu, Zn, Y, Cd, and In.
4. The method for preparing the iridium-based nanoparticle catalyst according to claim 1, characterized in that: In S1, the alkaline compound is one or more of ammonium carbonate, ammonium bicarbonate, ammonium chloride, ammonium oxalate, ammonium sulfate, ammonium hydroxide, ammonium nitrate, sodium hydroxide, and potassium hydroxide.
5. The method for preparing the iridium-based nanoparticle catalyst according to claim 1, characterized in that: In S3, the drying temperature is 70-90°C and the drying time is 24-48 hours.
6. The method for preparing the iridium-based nanoparticle catalyst according to claim 1, characterized in that: In S4, the dispersing method is grinding or ultrasound.
7. The method for preparing the iridium-based nanoparticle catalyst according to claim 1, characterized in that: In S4, the heating rate of the annealing is 1-5°C / min, the annealing atmosphere is argon, nitrogen or air, and the annealing pressure is normal pressure.
8. The method for preparing the iridium-based nanoparticle catalyst according to claim 1, characterized in that: In S2, the solvent is one or more of deionized water, ethanol, and isopropanol.
9. An iridium-based nanoparticle catalyst prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The catalyst is Ir x -M y -O 1-x-y Indicates that, 0.05≤x≤0.2, 0.25≤y≤0.
4.
10. Use of the iridium-based nanoparticle catalyst according to claim 9, characterized in that: The iridium-based nanoparticles are used as anode catalysts in a proton exchange membrane water electrolysis device.
Citation Information
Patent Citations
Method for preparation of water electrolysis oxygen evolution catalyst with silicon oxide molecular sieve as template
CN103055853B
Synthesis method of monodisperse nano-iridium oxide electrocatalyst
CN104437481B
Cited By
Sub-nanoparticle and preparation method and application thereof
CN120438635A
IrCo-based nanoparticle catalyst as well as preparation method and application thereof
CN121852973A